1981
DOI: 10.1002/zaac.19814800904
|View full text |Cite
|
Sign up to set email alerts
|

Acyl‐ und Alkylidenphosphane. XVII. Triacetylphosphan aus Tris(trimethylsilyl)phosphan

Abstract: Tris(trimethylsilyl)phosphan und Acetylchlorid im überschuß reagieren bei 0°C in Cyclopentan zu Chlortrimethylsilan und Triacetylphosphan 3a. Im Unterschied zum entsprechenden 2,2‐Dimethylpropionyl‐Derivat (Z)‐5 b sind die intermediär gebildeten Verbindungen (E)‐ und (Z)‐Acetyl‐[1‐(trimethylsiloxy)äthyliden]phosphan 5 a thermisch sehr instabil und konnten nicht rein isoliert, sondern nur NMR‐spektroskopisch charakterisiert werden. Die Isomeren unterscheiden sich kaum in ihren chem. Verschiebungen, aber stark i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Acylphosphines and their oxides are used as photoinitiators for radical-initiated polymerization [1][2][3][4] reactions used in the manufacture of consumer goods such as automotive coatings, adhesives, latex composition kits, and various dental and orthodontic materials. [5][6][7][8][9][10][11][12][13][14] Known methodologies for the synthesis of acylphosphines employ nucleophilic sources of phosphorus such as tris(trimethylsilyl)phosphine (P(TMS) 3 , TMS ¼ trimethylsilyl), [15][16][17] which is volatile, pyrophoric, toxic, expensive, and difficult to handle. 18 Transition metal-supported phosphines and phosphides have been used as a platform in niche syntheses of acylphosphines, though scope is limited and products remain bound to the metal center.…”
mentioning
confidence: 99%
“…Acylphosphines and their oxides are used as photoinitiators for radical-initiated polymerization [1][2][3][4] reactions used in the manufacture of consumer goods such as automotive coatings, adhesives, latex composition kits, and various dental and orthodontic materials. [5][6][7][8][9][10][11][12][13][14] Known methodologies for the synthesis of acylphosphines employ nucleophilic sources of phosphorus such as tris(trimethylsilyl)phosphine (P(TMS) 3 , TMS ¼ trimethylsilyl), [15][16][17] which is volatile, pyrophoric, toxic, expensive, and difficult to handle. 18 Transition metal-supported phosphines and phosphides have been used as a platform in niche syntheses of acylphosphines, though scope is limited and products remain bound to the metal center.…”
mentioning
confidence: 99%
“…We decided to work with the sodium t butylate aggregate NaPH 2 (NaO t Bu) x 1 ( x ≈2.5) [3,17] as an inexpensive and conveniently to use source of phosphorus for the synthesis of acylphosphines. Silyl phosphine TMS 3 P has severe drawbacks because it is a pyrophoric, toxic and expensive liquid [5,7,9,12,13] . Compound 1 was prepared in situ from red phosphorus, three equivalents of elemental sodium and an equimolar amount of t butanol as proton source.…”
Section: Resultsmentioning
confidence: 99%
“…In 1977, Becker prepared tris(pivaloyl)phosphine as side product with 23 % yield by reacting tris(trimethylsilyl)phosphine (TMS 3 P) with pivaloyl chloride [12] . Four years later, the same authors reported tris(acetyl)phosphine in a similar manner by reacting TMS 3 P with acetyl chloride [13] . Mislow and co‐workers studied the synthesis of tris(benzoyl)phosphine in 1979 and reported 13 C‐ and 31 P‐NMR spectra, which also contained resonance signals of the oxidized derivative [14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reactions with alcohols and water bis(trimethylsilyl) and (trimethylsilyl)phosphine can be synthesized;9 acetyl chloride in a molar ratio of 1:3 gives triacetylphosphine. 10 For the important reaction with 2,2-dimethylpropionyl chloride see Section 49.…”
Section: Propertiesmentioning
confidence: 99%